Ali so metode alternativne medicine v Sloveniji res nekaj povsem novega? = Methods of alternative medicine - are they really quite new in Slovenia? - Židov, Nena (Etnolog. Nova vrsta (Ljubljana), 2000)
The author establishes that many ideas, methods and techniques belonging to alternative medicine, which are nowadays imported, have a certain tradition in Slovenia, but that this tradition was discontinued for some time. She has found evidence of the following in the past: natural treatment of chronic diseases, homeopathy, dowsing or radiesthesia, bioenergy, treatment with medical herbs, crystals and metals, manipulative therapy, massages, diets and urinotherapy.
Keywords: ethnology; etnologija; ljudska medicina; alternativna medicina